Transparency, accountability, and governance: a literature review in the context of public hospitals - Nunes, Carlos (2023)
This study develops a literature review based on bibliometric analysis on the theme of transparency and accountability within the scope of governance of public hospitals, seeking to identify research lines, theories, research methods, and existing gaps through the analysis of scientific publications until 2020. The investigation followed the theoretical lens of transparency and accountability in the public sector to understand its framework within the scope of the governance of hospitals. Using the Bibliometrix software, and after the consultation process of the articles published in the Scopus and WoS databases, a sample with 118 articles was selected. It was found that, in the period between 2017-2020, approximately 85% of the publications were qualitative, and there is a growing trend in the study of transparency and accountability within the scope of governance of public hospitals. Transparency often appears interconnected with the accountability of agents (accountability), external communication policies (public reports), internal communication policies, and their comprehensibility. The predominance of publications of North American and Chinese origin was also noted. The study also identifies the scarcity of research using quantitative models that explore dependency relationships between the dimensions studied, limiting the comprehensibility of the interdependence between transparency practices and organizations' internal and external attributes. The study contributes to the knowledge about the interactions between transparency, accountability, and reporting within the scope of governance of public hospitals.